Excessive Alcohol Intake Induce Ketoacidosis Diabeticum - I Putu Agus Wijaya Putra; Tjokorda Prima Dewi Pemayun (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2026)
Diabetic ketoacidosis (DKA) is one of the most serious and life-threatening complications of diabetes mellitus (DM). DKA is characterized by the presence of hyperglycemia, metabolic acidosis, and ketosis. One of the precipitating factors of DKA is excessive alcohol consumption. Alcohol intake can adversely affect glycemic control by increasing the production of reactive oxygen species (ROS). Elevated ROS levels may lead to dysfunction and apoptosis of pancreatic beta cells, resulting in glucose intolerance and insulin resistance. This case report describes a 19-year-old female who presented to the emergency department with decreased consciousness, Kussmaul respiration, and shock. Random blood glucose level was 725 mg/dL. Arterial blood gas analysis revealed metabolic acidosis (HCO₃ 1.4 mmol/L, PCO₂ 13.4 mmHg, PO₂ 214.6 mmHg, tCO₂ 1.8 mmol/L, pH 6.64, and SaO₂ 97.8%). Additional laboratory findings included urea of 35.0 mg/dL and creatinine of 1.10 mg/dL. Urinalysis showed urine ketones +2, glucose +3, and leukocytes 5–10 per high-power field. The patient was diagnosed with diabetic ketoacidosis, acute kidney injury, and complicated urinary tract infection. Recommended management of DKA includes correction of dehydration, insulin therapy, correction of electrolyte imbalances, and identification of precipitating factors. Appropriate management can lead to a favorable prognosis in patients with DKA.